PERUBAHAN GOLONGAN DARAH PADA PENDERITA LEUKEMIA MIELOBLASTIK AKUT - Losen Adnyana, IW; Suega, K (journal of internal medicine, 2011)
We reported a case of acute leucemia (AML-M6) that experienced change of blood group. Leukemia is hematologicmalignancy with differentiation abnormality at grades haematopoetic stem cell that can make progressive expansión frommalignant clone cell in bone marrow and than spread to systemic circulation. In ABO blood system, group A with A antigenand anti B antibody, group B with B antigen and A antibody, O group without AB antigen and antibody. In this case, acuteleukemia be con! rmed with blood smear and bone marrow puncture. Changes of blood group known after remission inductionchemotherapy accordng to AML-M6 regiment. Post chemotherapy, there was changes O to A blood group according to ABOsystem. On family examination showed result of subgroup A of blood group previously. On acute leucemia or other hematopoiticdisease, there are two mechanism for explanation change of ABO blood system. The ! rst hematologic malignancy induced lossof ABO antigen due to inactivity of transferae A and B as the result was loss or decreased of antigen A and or B with simultantincrease of H antigen. Second, loss of ABH antigen in certain type of leucemia preceeding by loss of heterogenicity. ABO antigenwill reversed after proper treatment of leucemiaitself.